"I feel your pain" : factors influencing empathic concern for a suicidal peer - Sherinah Binte Rashid (2011)
This study had two aims: (1) Investigate the direct and interactive influence of situational characteristics (perceived controllability over one’s situation, closeness with one’s peer, and prior knowledge of suicidal others) and personality characteristics (level of allocentrism) on empathic concern experienced for a suicidal peer, and (2) Explore the applicability of Batson’s (1987) empathy-altruism model to the context of suicidality. To test these, an online survey was administered to 100 undergraduates, aged 19 to 26 years. Only closeness was a strong predictor of empathic concern, indicating a stronger influence of situational characteristics over personality characteristics. Implications of examining determinants of empathic concern and suggestions for facilitating empathic concern among young adults are discussed.